Crouzon syndrome - A rare case report - Kalanjiam, Vidhya; Manoharan, G.V. Murali Gopika (International Journal of Health Sciences, 2017)
Crouzon syndrome is the most common syndrome among the craniosynostosis group. Crouzon syndrome accounts for about 4.8% of all of them. It commonly has autosomal dominant inheritance with complete penetrance and variable expressivity from subtle to severe forms and characterized by craniosynostosis, exophthalmos, and hypoplastic maxilla with relative mandibular prognathism. Mutation of the fibroblast growth factor receptor-2 gene is responsible for the occurrence of this rare genetic disorder. Our paper reports the diagnosis of this rare syndrome in a young female patient based on clinical and radiographical features. Prompt and timely management of the syndrome has enabled this patient to lead a normal life despite the syndrome.